2015
DOI: 10.7314/apjcp.2015.16.8.3125
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Alternative Medicine Use Amongst Breast Cancer Patients in the Northern Region of Peninsular Malaysia

Abstract: Background: Breast cancer is a common cancer affecting women in Malaysia and the use of complementary/ alternative medicine (CAM) has been associated with delays in getting treatment. The aim of the study was to explore the use of CAM and the influencing factors in the Northern region of Peninsular Malaysia. Materials and Methods: This was a cross-sectional descriptive study on a convenience sample of 100 Malaysian breast cancer survivors. Findings: The reported use of CAM among the breast cancer survivors was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…In this study and similar to many local studies, ethnicity was found to be associated with CAM use where the Malays were observed to use CAM more than other ethnics [8,10]. Although some studies in Malaysia reported that there is no significant association between ethnicity and CAM, Malays was found to be the highest CAM user compared to Chinese and Indian [6,9,28,39].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In this study and similar to many local studies, ethnicity was found to be associated with CAM use where the Malays were observed to use CAM more than other ethnics [8,10]. Although some studies in Malaysia reported that there is no significant association between ethnicity and CAM, Malays was found to be the highest CAM user compared to Chinese and Indian [6,9,28,39].…”
Section: Discussionsupporting
confidence: 83%
“…To date, studies on CAM use amongst breast cancer patients in Malaysia are more focused on the prevalence and its associated factors [1,8,10,27]; type and pattern [9,28]; purposes [2]; knowledge [29]; and quality of life [7]. There is a scarcity of published reports on CAM use and its impact on cancer treatments.…”
Section: Introductionmentioning
confidence: 99%
“…These included herbal therapy, massage, acupuncture, acupressure, yoga, hypnotherapy, prayer therapy, and energy therapy. Herbal therapy is known to be popular among cancer patients worldwide, from the United Kingdom to numerous Asian communities (Damery et al, 2011; Hwang et al, 2015; Knight, Hwa, & Hashim, 2015). Studies reveal that the QoL of cancer patients who used additional herbal therapy differed from that of patients who underwent chemotherapy only (Hwang et al, 2015; Knight et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Herbal therapy is known to be popular among cancer patients worldwide, from the United Kingdom to numerous Asian communities (Damery et al, 2011; Hwang et al, 2015; Knight, Hwa, & Hashim, 2015). Studies reveal that the QoL of cancer patients who used additional herbal therapy differed from that of patients who underwent chemotherapy only (Hwang et al, 2015; Knight et al, 2015). In the United Kingdom, green tea, noni juice, ginger, aloe vera, and garlic were types of herbal therapy that were commonly used alongside chemotherapy (Damery et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Several experiences have been reported, particularly from Eastern countries. In patients with breast cancer, CAM was used by 70% of patients and was associated with higher education levels and household incomes, advanced cancer, and lower chemotherapy schedule compliance [ 6 ] and got information from television or radio [ 7 ]. More than 80% of all women with breast cancer reported using CAM, with 41% of them in a specific attempt to manage the disease [ 8 ].…”
Section: Introductionmentioning
confidence: 99%